Going the distance: are we losing patients along the multiple myeloma treatment pathway? - Terpos, Evangelos; Suzan, Florence; Goldschmidt, Hartmut (Critical reviews in oncology, hematology, 2018)
Despite data suggesting that individuals with multiple myeloma can benefit from receiving several lines of therapy, and guidelines recommending treatment after relapse, a recent European patient chart review found that only 61% of patients receive second-line treatment. The review found that factors such as old age and previous adverse events lead to physicians deciding not to treat after relapse. However, given the large number of regimens available, treatment can be tailored to individual patients’ needs and supportive care measures can help with the management of adverse effects. If approved therapies are not suitable for a patient, guidelines recommend registration in a clinical trial, yet only 7% of patients in the review were participating in such studies. A need for better education on the range of treatments available and their risk-benefit profiles is suggested. Access to new drugs should be examined to maximise the number of patients benefitting from them.